Translanguaging on ELT writing classroom during National students' exchange: Perceptions and practices - Styati, Erlik Widiyani; Irawati, Lulus (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to investigate translanguaging perceptions and practices in ELT writing classrooms during a national student exchange. It is to identify the perception and to determine the practices of translanguaging in students’ writing. This study used a survey design of quantitative research in nature. The survey involved 24 EFL students consisting of 23 females and 1 male who come from various universities in Indonesia. Those EFL students as the participants were assigned to fill the closed and open questionnaire about their perception oflanguage choice in writing. There are 15 closed statements and 5 open statements in the questionnaire. Besides that, a writing test was also used to learn the practices of translanguaging. The data were analyzed by using descriptive statistical analysis, to find a general description of the research data. The results show that the perceptions are classified into language choice, language brokering, and the use of translanguaging. The practices of translanguaging on students’ writing show that the average score of the student's writing is 76 based on the indicators of the student's writing which are measured based on the aspects of written production of content, organization, grammar, mechanics, and vocabulary. It indicates that translanguaging can help the students achieve the target of writing in English. Translanguaging also assists students in learning English, making meaning, and being more active in class during classroom activities. Students can talk about topics more freely, which helps them express themselves in their writing. HIGHLIGHTS : Translanguaging is the process by which bilinguals use diverse linguistic characteristics or modes of what are referred to as autonomous languages in order to enhance their communicative abilities. Translanguaging refers to the use of various languages in writing to improve the development of iintricate concepts. This method encourages authors to use their linguistic arsenal, fusing various languages together to communicate ideas in a richer, more complex way. Language learners consider translanguaging is helpful in educational contexts because it enables them to use their whole linguistic repertoire to improve their communication skills and understanding.